Cognitive Impairment Correlates Linearly with Mean Flow Velocity by Transcranial Doppler below a Definable Threshold - Randolph S. Marshall; Marykay A. Pavol; Ying Kuen Cheung; Iris Asllani; Ronald M. Lazar (Cerebrovascular Diseases Extra, 2020)
Introduction: Low cerebral blood flow can affect cognition in patients with high-grade asymptomatic internal carotid artery stenosis. Current clinical algorithms use stroke risk to determine which patients should undergo revascularization without considering cognitive decline. Although correlations between low-flow and cognitive impairment have been reported, it is not known whether a threshold exists below which such a correlation expresses itself. Such information would be critical in treatment decisions about whether to intervene in patients with high-grade carotid artery stenosis who are at risk for cognitive decline. Objective: To determine how reduced blood flow correlates with lower cognitive scores. Methods: Patients with ≥80% unilateral internal carotid artery stenosis with no history of stroke were recruited from inpatient and outpatient practices at a single, large, comprehensive stroke center. Patients underwent bilateral insonation of middle cerebral arteries with standard 2-Hz probes over the temporal windows with transcranial Doppler. Cognitive assessments were performed by an experienced neuropsychologist using a cognitive battery comprising 14 standardized tests with normative samples grouped by age. Z-scores were generated for each test and averaged to obtain a composite Z-score for each patient. Multivariable linear regression examined associations between mean flow velocity (MFV) and composite Z-score, adjusting for age, education, and depression. The Davies test was used to determine if there was a breakpoint for a non-zero difference in slope of a segmented relationship over the range of composite Z-score values. Results: Forty-two patients with unilateral high-grade internal carotid artery stenosis without stroke were enrolled (26 males, age = 74 ± 9 years, education = 16 ± 3 years). Average composite Z-score was –0.31 SD below the age-specific normative mean (range –2.8 to +1.2 SD). In linear regression adjusted for age, education, and depression, MFV correlated with cognitive Z-score (β = 0.308, p = 0.043). A single breakpoint in the range of composite Z-scores was identified at 45 cm/s. For MFV <45 cm/s, Z-score decreased 0.05 SD per cm/s MFV (95% CI: 0.01–0.10). For MFV >45 cm/s, Z-score change was nonsignificant (95% CI: –0.07 to 0.05). Conclusions: In high-grade, asymptomatic carotid artery stenosis, cognitive impairment correlated linearly with lower flow in the hemisphere fed by the occluded internal carotid artery, but only below a threshold of MFV = 45 cm/s. Identifying a hemodynamic threshold for cognitive decline using a simple, noninvasive method may influence revascularization decision-making in otherwise “asymptomatic” carotid disease.